Long-term conservation and rehabilitation of threatened rain forest patches under different human population pressures in West Africa - Neuenschwander, Peter; Bown, D.; Hedegbetan, G.C.; Adomou, A. (Pensoft Publishers, 2015)
The management schemes of four rain forest patches in southern Benin and south-western Nigeria, which led to the successful protection of numerous threatened plants and animals over the last 20 plus years, are analysed. Since climatic conditions are similar, tree composition depends largely on different availability of water and documented biodiversity mostly on the availability of taxonomic expertise. Management differs according to accessibility and human population pressure, from total closing off of the forest by an international institute near the mega-polis Ibadan to unmarked borders near Lanzron, a remote village in the lower Ouémé Valley, where foreigners are mostly excluded from visiting the site. In Benin, trees and wildlife (antelopes and monkeys) seem best protected where the local vodoun beliefs are adhered to. This is, however, not sufficient and development aid to support and benefit the local population is needed as exemplified in Zinvié. At the Ibadan and Drabo sites, long-term protection is assured by legally-binding land-titles. Since for all of Lanzron and part of Zinvié these are lacking securing them is a priority. In Ibadan, Nigeria, a major rehabilitation effort is concentrated on bringing relatively old grass land and former village sites under forest cover by planting local trees. Rehabilitation in Drabo, in southern Benin, relies on enriching the naturally occurring fallow succession with rare species from nearby threatened sacred forests. We demonstrate that reversing biodiversity loss is possible but requires a long-term commitment. Recommendations for protecting, stabilizing and enhancing similar small hotspots of biodiversity are made.